Cost analysis of corneal tissue processing: A scoping review protocol - Gustavo Moura Maidana; Marcos Antonio Ferreira Júnior; Felipe Machado Mota; Andréia Insabralde de Queiroz Cardoso; Bruna Dias Abes; Mayra Dias; Letícia Lima Meza (PLoS ONE, 2025)
Introduction Diseases affecting the cornea are a group of pathological conditions responsible for the main causes of blindness worldwide. Corneal transplantation aims to replace dysfunctional corneal tissue with a transparent tissue graft obtained from a deceased donor, which enables the full recovery of lost vision. Processes are initially performed to prepare the corneal tissue for transplantation in order for this transplant to be viable. There is a gap in knowledge regarding the costs of these processes. This review aims to carry out a robust, broad and current mapping of studies which analyze the costs of processing corneal tissue for transplantation. Objective The objective of this study is to map the evidence produced in the literature on cost analysis studies of corneal tissue processing. Materials and methods A scoping review will be conducted to map the topic, gather different research designs and identify the available scientific evidence on corneal tissue processing. To this end, a scoping review protocol was developed, registered in the Open Science Framework (accessed at: DOI 10.17605/OSF.IO/2X89U), following the good practices described by the Joanna Briggs Institute. The review report will be guided by the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews checklist. The data will be presented descriptively, with a summary of the studies found. The guiding research question of the study is: What is the scope of scientific evidence on the cost analysis of corneal tissue processing for transplants?